Effect of precursor solutions on the structural and optical properties of sprayed NiO thin films. (15th June 2017) - Gomaa, M.M.; Yazdi, G. Reza; Schmidt, Susann; Boshta, M.; Khranovskyy, V.; Eriksson, F.; Farag, B.S.; Osman, M.B.S.; Yakimova, R.
Abstract: Nickel oxide thin films were deposited by a simple and low-cost spray pyrolysis technique using three different precursors: nickel nitrate, nickel chloride, and nickel acetate on corning glass substrates. X-ray diffraction show that the NiO films are polycrystalline and have a cubic crystal structure, although predominantly with a preferred 111-orientation in the growth direction and a random in-plane orientation. The deconvolution of the Ni 2p and O 1s core level X-ray photoelectron-spectra of nickel oxides produced by using different precursors indicates a shift of the binding energies. The sprayed NiO deposited from nickel nitrate has an optical transmittance in the range of 60–65% in the visible region. The optical band gap energies of the sprayed NiO films deposited from nickel nitrate, nickel chloride and nickel acetate are 3.5, 3.2 and 3.43 eV respectively. Also, the extinction coefficient and refractive index of NiO films have been calculated from transmittance and reflectance measurements. The average value of refractive index for sprayed films by nickel nitrate, nickel chloride and nickel acetate are 2.1, 1.6 and 1.85 respectively. It is revealed that the band gap and refractive index of NiO films by using nickel nitrate corresponds to the commonly reported values. We attribute the observed behavior in the optical band gap and optical constants as due to the change of the Ni/O ratio. Highlights: The sprayed NiO films by using different precoursors have a cubic crystal structure and a predominant 111-orientation. The variation of the optical properties of NiO films by using different precursors is due to the changes in the Ni/O ratio. The sprayed NiO films by nickel nitrate have a high degree of crystallinity, low roughness and high optical transmission. Optoelectronic.